Changes in the biochemical constituents of gills of Cirrhinus mrigala (Ham.) following exposure to metals - Virak, S; Sharma, A (Indian Journal of Fisheries, 2011)
Studies were conducted to assess the effects of acute toxicity of nickel and chromium on fingerlings of the Indian major carp Cirrhinus mrigala (Ham.). Ninety six hour LC50 values of nickel and chromium were calculated to be 34.00 and 70.00 mg/I respectively, whereas the safe concentrations were 13.60 mg/l for nickel and 31.50 mg/l for chromium. Exposure of C. mrigala to safe and sublethal concentrations (1/2 of 96 hour LC50) of nickel (13.6 and 17.00 mg/l) and chromium (31.50 and 35.00 mg/l) for 45 days caused significant decline in the protein and carbohydrate contents of gills. After 45 days of exposure, when fish were transferred to metal-free water for 18 days, the levels of proteins and carbohydrates improved considerably.